Utilization Of Contemporary Methodologies In The Instruction Of The Native Language - Berdiyeva Nilufar Ibodullayevna (Euro Asian Journal Publishing, 2024)
This article explores the benefits of integrating cooperative educational technologies to improve oral literacy, emphasizing their application in native language instruction within the Uzbekistan context. The inquiry specifically examines modern methodologies utilized for teaching the native language, with the primary goal of elucidating the role of cooperative technologies in advancing oral literacy skills
Keywords: literature education; educational landscape; Uzbek language